Optimal Allocation of Slope Ecological Restoration for the Climate Change Mitigation and Natural Function Improvement - Qin, Tianling; He, Shan; Liu, Shanshan; Nie, Hanjiang; Dong, Biqiong; Lv, Xizhi (Frontiers in Earth Science, 2022)
The key to dealing with extreme problems at watershed or region scales in the context of climate change is the "de-extremalization" of hydrological processes. The foundation lies in how to optimize the allocation of ecological restoration on slopes to mitigate the extreme impacts of climate change on hydrological processes and improve ecological service functions. Previous studies focused on analyzing the direct effects of slope land use, vegetation distribution, or historical pattern of ecological restoration on runoff processes. This study developed a slope ecological restoration evaluation system to evaluate the naturalness, functional types and functional coordination of slope ecological restoration at different historical stages and quantitatively identified the mitigation effect on climate change in the future. It was applied to the Huangshui River Basin (above Minhe County) in Qinghai Province, China. Based on the land suitability evaluation methods, a set of layout schemes were constructed. The runoff mutation and ecological function of different schemes under climate change were evaluated, and the highly suitable scheme was selected as the optimal scheme. Compared with the current situation, the coupling coordination degree index of the scheme would increase from 0.32 to 0.59. Meanwhile, the runoff and coefficient of variation would be decreased by 30% and 60% respectively during the wet season under the high-emission scenario RCP8.5. This study closely links the ecological construction of slopes with the response to extreme climates, which provides technical methods and practical support for the optimization of regional ecological patterns and scientific water governance modes.